2009
DOI: 10.1007/s12199-009-0090-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Noto-Peninsula earthquake and maternal postnatal depression and child-rearing

Abstract: Objective The aim of our study was to explore the relationship between a medium-scale earthquake and maternal depression and child-rearing in a depopulated community in the Noto Peninsula of Japan. Methods Three months after a major earthquake, selfrating questionnaires were distributed to women who were pregnant at the time of the earthquake or who became pregnant immediately thereafter, and who were receiving care at any of four major hospitals in the most devastated area. A total of 155 women who had given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…This finding is in line with a previous study of pregnant women affected by Hurricane Katrina, which found that maternal depression was associated with a loss of resources, including social support network and daily routine [ 27 ]. Another post-earthquake study from Japan reported that mothers’ EPDS score was associated with their satisfaction with delivery, including obstetrical care [ 28 ]. Moreover, an interruption in care could be accompanied by evacuation and other disaster-related incidents, which may further affect maternal mental health.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with a previous study of pregnant women affected by Hurricane Katrina, which found that maternal depression was associated with a loss of resources, including social support network and daily routine [ 27 ]. Another post-earthquake study from Japan reported that mothers’ EPDS score was associated with their satisfaction with delivery, including obstetrical care [ 28 ]. Moreover, an interruption in care could be accompanied by evacuation and other disaster-related incidents, which may further affect maternal mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Because the number of clinical cases was small in multivariate logistic regression analyses in the within-3-months group and in the 4-6-months group separately, the after-disaster group included both the within-3-months group and the 4-6-months group for multivariate logistic regression analyses. For the risk factors for perinatal depression that were related to the disaster, previous studies have found that exposure to storm, 27 loss of resources, 28 earthquake experience, 29 , 30 anxiety about earthquakes, 31 , 32 and exposure to tsunami 2 were more likely to cause depression in pregnant and postnatal women who were affected by natural disasters. In the present study, we found that the destruction of their home and dissatisfaction with their living conditions were significant risk factors for postpartum depression among women in the after-disaster group.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the risk factors for perinatal depression related to the disaster, previous studies found that exposure to the storm (Xiong et al 2010 ), loss of resources (Ehrlich et al 2010 ), high earthquake exposure (Qu et al 2012 ), and anxiety about earthquakes (Hibino et al 2009 ) were more likely to cause depression in pregnant and postnatal women affected by natural disasters. In the present study, we found that exposure to the tsunami was a significant risk factor for postnatal depression.…”
Section: Discussionmentioning
confidence: 99%